Membangun Karakter Generasi Bangsa untuk Pekerjaan Masa Depan Digital Content Creator melalui Pendidikan Moral - Muh. Ali, Muh. Ali; Murdiansyah, Eko Bambang (Penerbit Widina, Widina Media Utama, 2025)
The rapid development of the digital ecosystem has opened new career opportunities as digital content creators; however, the increasing volume of content production is not always followed by ethical behavior, integrity, and social responsibility. This condition underscores the urgency of moral education capable of developing the character of young generations in addressing ethical challenges in digital spaces. This study aims to analyze the role of moral education in shaping the ethical character of prospective content creators and to examine the effectiveness of a moral education model based on project-based learning and digital ethics. Using a mixed-methods approach with a quasi-experimental pretest–posttest control group design and a qualitative approach through in-depth interviews and focus group discussions (FGDs), this study involved 306 respondents determined using the Slovin formula from a population of 1,305 participants of digital content training. The intervention consisted of digital ethics modules and project-based learning delivered over eight weeks. The results indicate a significant increase in ethical character scores, including integrity, social responsibility, self-regulation, and cultural awareness in the intervention group compared to the control group. T-tests and ANCOVA showed meaningful differences in mean scores (p 0.05), while content analysis of participants’ projects demonstrated improved compliance with copyright, accuracy of information, and cultural sensitivity. Qualitative findings reinforced that ethical reflection processes and real content production experiences contributed to the internalization of moral values. This study concludes that integrated project-based moral education is effective in shaping the ethical character of the digital generation and is relevant for implementation within vocational curricula, higher education, and creative industry training programs.ABSTRAKPerkembangan pesat ekosistem digital telah membuka peluang karier baru sebagai digital content creator, namun peningkatan produksi konten tidak selalu diikuti perilaku etis, integritas, dan tanggung jawab sosial. Kondisi tersebut menegaskan urgensi pendidikan moral yang mampu membangun karakter generasi muda dalam menghadapi tantangan etika di ruang digital. Penelitian ini bertujuan untuk menganalisis peran pendidikan moral dalam pembentukan karakter etis calon pembuat konten serta menguji efektivitas model pendidikan moral berbasis project-based learning dan etika digital. Menggunakan metode mixed-methods dengan desain kuasi-eksperimental pretest–posttest control group serta pendekatan kualitatif melalui wawancara mendalam dan FGD, penelitian ini melibatkan 306 responden yang ditentukan menggunakan rumus Slovin dari populasi 1305 peserta pelatihan konten digital. Intervensi berupa modul etika digital dan pembelajaran berbasis proyek diberikan selama delapan minggu. Hasil penelitian menunjukkan peningkatan signifikan pada skor karakter etis, meliputi integritas, tanggung jawab sosial, regulasi diri, dan kesadaran budaya pada kelompok intervensi dibandingkan kelompok kontrol. Uji t dan ANCOVA mengindikasikan perbedaan rerata yang bermakna (p 0.05), sementara analisis konten produk menunjukkan peningkatan kepatuhan terhadap hak cipta, akurasi informasi, dan sensitivitas budaya. Temuan kualitatif memperkuat bahwa proses refleksi etis dan pengalaman produksi konten nyata berkontribusi pada internalisasi nilai moral. Penelitian ini menyimpulkan bahwa pendidikan moral terintegrasi berbasis proyek efektif untuk membentuk karakter etis generasi digital dan relevan diterapkan pada kurikulum vokasional, pendidikan tinggi, dan pelatihan industri kreatif.